Empowering thinking and moral formation in Muslim women through the Philosophical Inquiry (PI) approach - Abdullah, Norillah; Abdelmagid, Mohamed (al-Burhān Journal of Qurʾān and Sunnah Studies, 2023)
Philosophical inquiry (PI) is one of the approaches educators employ to help develop thinking skills and moral education among students so that they can understand their goals and the purpose of life in this world. Meanwhile, much has been said about the social problems involving Muslim women in Malaysia which are due to the lack of thinking skills and religious understanding. For this reason, this study attempts to highlight the PI method which integrates the Socratic questioning approach to help address the issue and lead to moral formation. This would allow women to explore their thoughts and generate rational ideas and choices to achieve understanding and sound judgments (hikmah) and finally empower them in executing their roles and tasks as Muslimah who hold the responsibility as daughters and sisters who will be future wives and mothers in the society, and carry out their Amanah as the Khalifah of Allah in this world.